Comparison of Low-Dose Granisetron (0.1 Mg) and Dexamethasone (8 Mg) With Ondansetron (4 Mg) and Dexamethasone (8 Mg) for Prevention of Postoperative Nausea and Vomiting Following Laparoscopic Surgery - Dr. Abhinav Banerjee; Dr. Gesu Mehrotra, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Postoperative nausea and vomiting (PONV) are common complications following laparoscopic surgery, adversely affecting patient recovery and satisfaction. Effective prophylaxis is essential to enhance postoperative outcomes. Methods: This double-blind, prospective, randomized study was conducted at the Department of Anaesthesia and Critical Care, Tata Main Hospital, Jamshedpur. Eighty adult patients (ASA I-II, aged 18-60 years) undergoing elective laparoscopic surgery under general anesthesia were randomized into two groups. Group I received dexamethasone 8 mg and ondansetron 4 mg intravenously, while Group II received dexamethasone 8 mg and granisetron 0.1 mg intravenously. PONV incidence, nausea scores (Verbal Rating Scale), vomiting episodes, rescue antiemetic and analgesic requirements, and side effects were monitored at multiple postoperative intervals up to 48 hours. Results: Group A (dexamethasone + ondansetron) demonstrated significantly lower nausea scores at 30 minutes, 1 hour, 2 hours, and 4 hours postoperatively (p<0.05). The incidence of moderate to severe nausea was higher in Group B (dexamethasone + granisetron) (p=0.01). Complete response rates were significantly greater in Group A (20%) compared to Group B (5%) (p=0.01). The requirement for rescue antiemetics was higher in Group B (30% vs. 10%, p=0.01). No significant differences were observed in vomiting incidence or side effects between the groups. Conclusion: The combination of low-dose granisetron (0.1 mg) with dexamethasone (8 mg) is less effective than ondansetron (4 mg) with dexamethasone (8 mg) in preventing PONV following laparoscopic surgery. Ondansetron with dexamethasone provides superior prophylaxis, resulting in lower nausea scores and reduced need for rescue antiemetics.